CHARACTER EDUCATION VALUES IN SEMIOTIC MEANING OF LEGEND OF JAVANESE SCRIPT - Fitriana Kartika Sari; Sarwiji Suwandi; Supana Supana (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2018)
The story of Javanese script are spoken by hereditary that contains the character of educational values implicitly. This research aims to analyze the semiotic meaning and the implicit character educational values in the story. Source of data this research is Seneng Maca Aksara Jawa published by Percada. This research used descriptive qualitative method and used semiotic approach by Charles Sander Peirce. Data were obtained by reading text story of Javanese script and then analyze about sign, meaning of sign, and the character of educational values in it. The findings of the research showed: (1) the legend of Javanese script delivered by icons, indexes, and symbols, (2) the semiotic meaning of story of Javanese script contains character educational values, namely: religious, hard work, democratic, curiosity, recpect for achievement, love of peace, social awareness, and responsibility. The character educational values in the semiotic meaning of story of Javanese script were relevant with the values which established by Ministry of National Education. Moreover, it can be benefitted as contextual materials based on character of education in learning process of Javanese language appropriate with the Curriculum of 2013.Keyword: semiotic, Javanese script, character educationNILAI-NILAI PENDIDIKAN KARAKTER DALAM MAKNA SEMIOTIK LEGENDA AKSARA JAWAAbstrakLegenda aksara Jawa yang dituturkan turun-temurun mengandung nilai-nilai pendidikan karakter secara tersirat. Penelitian ini bertujuan menganalisis makna semiotik dan muatan nilai-nilai pendidikan karakter yang tersirat di dalamnya. Sumber data penelitian berupa buku Seneng Maca Aksara Jawa terbitan Percada. Penelitian deskriptif kualitatif ini menggunakan pendekatan semiotik Charles Sander Peirce. Data penelitian diperoleh dengan membaca secara cermat teks legenda aksara Jawa kemudian mengkaji tanda, makna tanda, serta muatan nilai-nilai pendidikan karakter di dalamnya. Selanjutnya diperoleh temuan data sebagai berikut: (1) legenda aksara Jawa mengandung tanda-tanda berupa ikon, indeks, dan simbol; (2) makna semiotik legenda aksara Jawa mengandung nilai-nilai pendidikan karakter, yaitu: religius, kerja keras, demokratis, rasa ingin tahu, menghargai prestasi, cinta damai, peduli sosial, dan tanggung jawab. Nilai-nilai pendidikan karakter tersebut relevan dengan nilai-nilai pendidikan karakter yang ditetapkan oleh Kementerian Pendidikan Nasional sehingga dapat dimanfaatkan sebagai sebagai materi kontekstual berbasis pendidikan karakter pada proses pembelajaran Bahasa Jawa sesuai dengan tuntutan Kurikulum 2013.Kata kunci: semiotik, aksara Jawa, pendidikan karakter.